Electrical Impedance Tomography to Measure Spirometry Parameters in Chronic Obstructive Pulmonary Disease Patients - Vargas Luna, Francisco Miguel; Kashina, Svetlana; Riu Costa, Pere Joan; Casan Clarà, Pere; Balleza Ordaz, José Marco (Revista Mexicana de Ingenieria Biomedica, 2022)
Spirometry is a test for the diagnosis of chronic obstructive pulmonary disease. It is a technique that can be intolerant due to the essential use of a mouthpiece and a clamp. This study proposes the use of electrical impedance tomography to measure respiratory parameters. Patients underwent spirometry and three respiratory exercises. The impedance signals were convolved, and the resultant was analyzed by fast Fourier transform. The frequency spectrum was divided into seven segments (R1 to R7). Each segment was represented in terms of quartiles (Q25%, Q50%, Q75%). Each quartile of each segment was correlated with the spirometric parameters to obtain a fitting equation. FVC was correlated 70% with the 3 quartiles of R7, 3 equations were obtained with a fit of 60%. FEV1 correlated 70% with the Q50% of R7, obtaining an equation with a fit of 40%. FEV1/FVC correlated 69% with Q75% of R2, obtaining an equation with a fit of 60%. Spirometric parameters can be estimated from the implied carrier frequency components of the ventilatory impedance signal.